A retrospective comparison of first and second opinion histopathology with patient outcomes in veterinary oncology cases (2011–2019). (23rd August 2021) - Laliberté, Sarah M.; Poirier, Valerie J.; Pinard, Christopher J.; Hocker, Samuel E.; Foster, Robert A.
Abstract: Mandatory second opinion histopathology is common practice in human surgical pathology. It is intended to confirm the original diagnosis or identify clinically significant discrepancies, which could alter the course of disease, cost of treatment, patient management or prognosis. This retrospective analysis aimed to evaluate agreement between first and second opinion histopathology cases, examine their correlation with natural history of disease and investigate the rationale for pursuing this test. Medical records from 2011 to 2019 were reviewed, identifying 109 cases where second opinion histopathology was sought. Reasons for seeking second opinion and clinical disease course were also reviewed to determine whether case progression favoured first or second opinion findings in cases of diagnostic disagreement. Diagnostic disagreement was found in 49.5% of cases. Complete diagnostic disagreement (a change in degree of malignancy or tumour type) occurred in 15.6% cases and partial disagreement (a change in tumour subtype, grade, margins and mitotic count) occurred in 33.9%. Major disagreement (a change in diagnosis resulting in alteration of treatment recommendations) occurred in 38.5% of cases. The most common reasons for seeking second opinion were an atypical/poorly differentiated tumour (31.2%; 34/109) or a discordant clinical picture (24.8%; 27/109). Among cases with any form of disagreement, natural history of disease favoured second opinion findings in 33.3%. The first opinion was favoured over the second in a single case. These findings reinforce previous literature supporting a role for second opinion histopathology in optimizing therapy and predicting outcomes in veterinary oncology, particularly in cases where diagnosis is in question based on the overall clinical picture.